PENGARUH INOVASI DAN KREATIVITAS CLAY MAGNET TERHADAP MINAT BELI MASYARAKAT - Devi Agustina; Dian Sudiantini, Freely Aldian Adam, Kamilah Kanaya Azies, Muhammad Aldi Satrio, dan Siti Aulia Iska (CV. Adiba Aisha Amira, 2024)
In this research, magnetic clay products have been made. This product can be marketed in various shops, such as souvenir shops, accessories shops, and various other marketplaces. This clay was developed so that it can produce new innovations that can be used to beautify the appearance of items made from aluminum, iron and the like, such as refrigerators, microwaves and air fryers. When making clay, creativity is needed to produce unique and attractive designs, as well as the quality of the materials used. From the research that has been carried out, the results obtained show that this product is an innovation and creativity regarding clay magnets which has a significant influence on people's buying interest. So, manufacturers need to continue to innovate and be creative to meet consumer needs and preferences.